The Polish Nobles’ Democracy: between Ancient and Modern Democracy - Krzywoszynski (Philosophia, 2021)
The aim of the article is to present the Polish Nobles’ Democracy as an example of a system that lies between the ancient and modern forms of democracy. The Polish tradition, both in the ideological and institutional solutions of democracy from the half of 15th century to the end of 18th century, was the link between the ancient and modern rule of the people. The abuse of some institutions and rhetoric became the cause of the fall of the Polish-Lithuanian Commonwealth at the end of 18th century. In addition to much criticism of this system on the part of Montesquieu, Voltaire and Frederick II, it also had its defenders and advocates, such as Rousseau or Schiller.